«Cuando yo ya no pueda hacerlo, nadie lo haráa»: La conservación de la agrobiodiversidad en tiempos de migración - Baldinelli, M.G. (Bioversity International, 2018)
This research explores the connections between agrobiodiversity conservation and indigenous farmers’ rural-urban migration in the Altiplano Norte of Bolivia. Two trends are identified and analysed: agronomic simplification, as part of a process of deagrarianisation; and agrobiodiversity reinvention, taking shape in a period in which the indigenous roots of Bolivia, native crops and traditional dishes experience a revival in discourse and food practices. Temporary and return migrants are important characters in this process, as innovators and crucial allies for urban-based stakeholders promoting agrobiodiversity conservation.